Resolusi Konflik Pertanahan di Kabupaten Tebo Provinsi Jambi (Studi tentang Desa Lubuk Mandarsah dengan PT. Wira Karya Sakti) - Diah Arimurti; Fitriyah .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
The conflict between PT. Wira Karya Sakti Village Community Lubuk Mandarsah isin the form of land grabbing. Society claiming it is public land, while the company claims itis the firm ground. Whereas in the Ministerial Decree No. 744/1996, applicable provisions iffound areas of the township and community gardens, these areas have become the exceptionand excluded from the company's concession area.This study aims to determine the root causes of conflict and to find the government infacilitating a conflict resolution process. The methodology used in this research is descriptivequalitative method, which is appropriate to describe the state of the real conditions of datacollection was done by in-depth interviews of the informants are considered to know clearlyseated problems. It also synthesize several documents that are considered important in thisstudy.The results showed that the root of the problem that gave rise to conflicts between thevillagers of Lubuk Mandarsah with PT. Wira Karya Sakti is dominated by the factor ofinterest. In this conflict there is triangulation interests include psychology interests, and theinterests of procedural substansional. Step settlement ever done through the establishment ofthe Conflict Resolution Team by the Governor of Jambi. However, in the progress of theConflict Resolution Team is not optimal. This is because the process of formation of ConflictResolution Team not only earnest in strong shape to accommodate the demands of thedemonstrators. Until now, the conflict has not been completed, but could subside because ofthe approach and the cooperation of the parties in conflict do.